1983
DOI: 10.1029/jb088ib11p09407
|View full text |Cite
|
Sign up to set email alerts
|

Collision, rotation, and the initiation of subduction in the evolution of Sulawesi, Indonesia

Abstract: The island of Sulawesi, Indonesia, has been shaped and deformed as a result of collision with the Sula platform, a sliver of continental material from the northern margin of Australia‐New Guinea. The collision has resulted in rotation of the north volcanic arm of Sulawesi and the development of the accretionary wedge of the North Sulawesi trench. The North Sulawesi trench changes laterally from a zone of no active deformation in the eastern part to a wide accretionary wedge in the west. Early stages of thrusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
4

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 23 publications
3
102
0
4
Order By: Relevance
“…Bathymetry from ETOPO5. by Silver et al [1983a], but we suggest that the intersection of the Sangihe arc with the North Sulawesi trench has modified the kinematics of the Sula block, by causing it to pivot about a nearby pole of rotation.…”
Section: A22 Present-day Examples Withoutmentioning
confidence: 99%
“…Bathymetry from ETOPO5. by Silver et al [1983a], but we suggest that the intersection of the Sangihe arc with the North Sulawesi trench has modified the kinematics of the Sula block, by causing it to pivot about a nearby pole of rotation.…”
Section: A22 Present-day Examples Withoutmentioning
confidence: 99%
“…Ophiolites in East Sulawesi (Kündig 1956;Silver et al 1983), derived from the ocean north of the Sula Spur, were thrust southwards onto the continental crust of the Sula Spur in East Sulawesi beneath the North Sulawesi forearc. After this collision, continued northwards movement of Australia was absorbed in several ways, including the subduction of oceanic crust at the Java trench, the broad nonrigid counter-clockwise rotation of SE Asia (Borneo, West Sulawesi, Java) and contraction and uplift in East and SE Sulawesi.…”
Section: Regional Backgroundmentioning
confidence: 99%
“…Hamilton 1979;Cardwell et al 1980). The Tolo trough has been recognized as a thrust (Silver 1981;Silver et al 1983;Hinschberger et al 2000Hinschberger et al , 2003, but not identified as an incipient subduction zone. The Sula deep has not been discussed before.…”
Section: Subduction Initiation: Sulawesi-philippinesmentioning
confidence: 99%
“…The island of Sulawesi appears to be a major suture zone along which a large oceanic basin (probably the Neotethys) was subducted (Hamilton, 1979;Silver et al, 1983aSilver et al, , 1983b. Along this suture zone, the Banda and Celebes-Sulu blocks were welded together in middle Miocene time (Kundig, 1956).…”
Section: Tectonic Framework Of the Celebes-sulu Basinsmentioning
confidence: 99%